Combined minimally invasive vagal cranial nerve and trigeminocervical complex peripheral nerve stimulation produces prolonged improvement of severe painful peripheral neuropathy and hyperglycemia in type 2 diabetes - Staats, Peter S.; Staats, Alyssa; Mikhaiel, Brittny; Chen, Jason; Azabou, Eric; Rangon, Claire-Marie (Frontiers in Neuroscience, 2025)
IntroductionDiabetic Peripheral Neuropathy (DPN), a debilitating complication of type 2 diabetes mellitus (T2DM), stems from bioenergetic failure and reduced vascular endothelial growth factor-A expression (VEGF-A), persisting despite optimal glycemic control. The meteoric rise of “diabesity”—the coexistence of obesity and T2DM—underscores the ongoing failure of symptom control strategies and the critical need to immediately address the root cause of metabolic dysfunction and neuropathic pain.MethodsAn analysis was performed on patients who received combined minimally invasive auricular vagus cranial nerve stimulation (aVNS) and trigeminocervical complex (TCC) peripheral nerve stimulation in 83 Native American patients (91 initial, 8 lost to follow-up) with severe T2DM and DPN pain who were offered stimulation in the routine course of clinical care. Participants were implanted on branches of their vagal and trigeminal cranial nerves, along with their upper cervical peripheral nerves and stimulated for 19 days prior to explantation. Numerical Rating Pain Scores (NRS) and mean blood glucose levels were measured at 30-, 60-, and 90-days post-explant.Results and discussionNotable results include: NRS pain scores dropping 87% (7.92 to 1.04), mean blood glucose decreasing 37% (209 to 121 mg/dL), and HbA1c levels falling from 8.9% to 5.8% at 90 days. These improvements were all sustained for an average of 7.85 months of follow up. Additionally, a random subset decreased 80% of all pain and diabetes medications. This efficacy surpasses prior outcomes from cervical VNS alone, highlighting the synergy of targeting both the vagal and trigeminal cranial nerves along with the trigeminocervical complex.DiscussionThese findings position combined minimally invasive aVNS and TCC peripheral nerve stimulation as a promising immediate therapy for the current DPN and diabesity crisis, as well as a potential non-pharmacologic alternative for the management of type 2 diabetes.